The image of a Russian emigrant on the example of Alexander Galich’s live and works - Pełka, Artur (Migracja w języku, literaturze i kulturze, 2020)
Influenced by events related to the spectacular protests held in Austrian refugee transit camps at the turn of 2012/13, Elfriede Jelinek created the text “The Charges” for the stage, borrowing its title from Aeschylus. This text soon became the most frequently staged – and not only – on German- speaking stages, a poignant documentary of the refugee drama. Moreover, it was updated several times by the writer, by adding more parts to it until December 2015. The resulting pentalogy not only documents the course of the mass exodus of those seeking refuge from the war, but also critically addresses its causes and, above all, the refugee policy of European countries and the related media manipulation, as well as – last but not least – the attitude towards the refugees of ordinary Europeans. In doing so, the Nobel Prize winner deconstructs the canonical texts of culture, thereby demythologizing the alleged foundation of humanism or Christian morale in Europe. An important element of this dismantling is the generation of “effects of the uncanny”, consisting in recalling the ghosts of the victims of past wars and extermination, including above all the victims of Nazi genocide. Jelinek’s text as an artistic intervention not only restores the idea of engaged theatre, but also – despite its pessimistic, as it were – neo-existentialist’ tone – advocates a model of the ‘remembered future’.